Pattern Formation in Dipolar Cold Atomic Quantum Gases Confined by a Flattened Trap - Al-Suhaili,Younis Tiea Harby (2025)
This thesis investigates the pattern formation of supersolid states in dipolar Bose-Einstein condensates (BECs) of highly magnetic Dysprosium-162 confined in a flattened trap geometry. This is done by solving the extended Gross-Pitaevskii equation (eGPE), a framework that was developed to examine BECs. The eGPE incorporates contact interaction, the dipole-dipole interaction (DDI), and quantum fluctuations via the Lee-Huang-Yang (LHY) correction. The flat trap modifies the potential landscape by modifying the interplay between the different interactions, in comparison to the more traditional harmonic trap. Key findings include the emergence of a ring phase characterized by a central density minimum, isolated droplets arranged symmetrically in a ring form at low particle numbers and contact interaction strengths, and stripe-like patterns as an intermediate phase between the previous two. The competition between the anisotropic dipole-dipole attraction, repulsive contact interactions, and stabilizing quantum fluctuations is what gives rise to these unique phases. This work emphasizes the crucial role that trap geometry plays in determining which phase the supersolid takes on.